Description of a new species of Xenopholis (Serpentes: Colubridae) from the Cerrado of Bolivia, with comments on Xenopholis scalaris in Bolivia - Jansen, Martin; Álvarez, Lucindo Gonzales; Köhler, Gunther (Zootaxa, 2009)
We describe a new species of Xenopholis from the Chiquitano Region in the eastern lowlands of Bolivia. The new species can be identified as member of the genus Xenopholis by its vertebral morphology. The new species differs from the other two species of Xenopholis in its unique, uniform dorsal color pattern. It further differs from X. scalaris by having two prefrontals and a narrow septum within each neural spine and perpendicular to its long axis. For X. scalaris we present new records from Bolivia, including the highest altitudinal record for the species and genus (Serranía Beu in the Pilón Lajas Reserve, Department of La Paz, 1500 m).